Hydrogen Storage in Deep Saline Aquifers: Non-Recoverable Cushion Gas after Storage - Katarzyna Luboń; Radosław Tarkowski (Energies, 2024)
Underground hydrogen storage facilities require cushion gas to operate, which is an expensive one-time investment. Only some of this gas is recoverable after the end of UHS operation. A significant percentage of the hydrogen will remain in underground storage as non-recoverable cushion gas. Efforts must be made to reduce it. This article presents the results of modeling the cushion gas withdrawal after the end of cyclical storage operation. It was found that the amount of non-recoverable cushion gas is fundamentally influenced by the duration of the initial hydrogen filling period, the hydrogen flow rate, and the timing of the upconing occurrence. Upconing is one of the main technical barriers to hydrogen storage in deep saline aquifers. The ratio of non-recoverable cushion gas to cushion gas (NRCG/CG) decreases with an increasing amount of cushion gas. The highest ratio, 0.63, was obtained in the shortest 2-year initial filling period. The lowest ratio, 0.35, was obtained when utilizing the longest initial filling period of 4 years and employing the largest amount of cushion gas. The presented cases of cushion gas recovery can help investors decide which storage option is the most advantageous based on the criteria that are important to them.